2010
DOI: 10.5194/acp-10-5391-2010
|View full text |Cite
|
Sign up to set email alerts
|

Spectral optical properties of long-range transport Asian dust and pollution aerosols over Northeast Asia in 2007 and 2008

Abstract: Abstract. As a part of the IGAC (International Global Atmospheric Chemistry) Mega-cities program, aerosol physical and optical properties were continuously measured from March 2007 to March 2008 at an urban site (37.57 • N, 126.94 • E) in Seoul, Korea. Spectral optical properties of long-range transported Asian dust and pollution aerosols have been investigated based on the year long measurement data. Optically measured black carbon/thermally measured elemental carbon (BC/EC) ratio showed clear monthly variati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 46 publications
5
27
0
1
Order By: Relevance
“…The spectral dependence and range of LIVAS SSA values are similar to the values provided in the Dubovik et al (2002) climatology and references therein, whereas the CALIPSO SSA has lower values which also agree with other studies (e.g., Eck et al, 1998Eck et al, , 2003. The polluted dust SSA spectral dependence is similar for both models but different to that of dust mixtures with smoke and pollution presented in the literature (e.g., Jung et al, 2010;Holler et al, 2003). Finally, the clean marine SSA for both models agrees very well with other studies in the literature (e.g., Dubovik et al, 2002;Hasekamp et al, 2011).…”
Section: Amiridis Et Al: Livas: a 3-d Multi-wavelength Aerosol/clsupporting
confidence: 79%
See 1 more Smart Citation
“…The spectral dependence and range of LIVAS SSA values are similar to the values provided in the Dubovik et al (2002) climatology and references therein, whereas the CALIPSO SSA has lower values which also agree with other studies (e.g., Eck et al, 1998Eck et al, , 2003. The polluted dust SSA spectral dependence is similar for both models but different to that of dust mixtures with smoke and pollution presented in the literature (e.g., Jung et al, 2010;Holler et al, 2003). Finally, the clean marine SSA for both models agrees very well with other studies in the literature (e.g., Dubovik et al, 2002;Hasekamp et al, 2011).…”
Section: Amiridis Et Al: Livas: a 3-d Multi-wavelength Aerosol/clsupporting
confidence: 79%
“…For the dust type, the LIVAS size distribution has fewer fine particles than the CALIPSO model, in agreement with the AERONET climatology of Dubovik et al (2002) and findings of experimental campaigns dedicated to mineral dust characterization (e.g., McConnell et al, 2008;Weinzierl et al, 2009;Müller et al, 2011;Toledano et al, 2011). For the polluted dust type both models seem to fall within the range of the large variability reported in the literature for dusty mixtures (Eck et al, 1999;Jung et al, 2010). The more pronounced fine mode in the LIVAS model resembles the size distributions of dust and pollution mixtures .…”
Section: Amiridis Et Al: Livas: a 3-d Multi-wavelength Aerosol/clsupporting
confidence: 72%
“…The sampled aerosol was then passed through a multichannel parallel-plate denuder with a carbon-impregnated filter to remove semivolatile organic vapors, and then collected on a quartzfiber filter. The sampled aerosol was analyzed based on the thermal-optical transmittance (TOT) protocol for pyrolysis correction and the NIOSH (National Institute for Occupational Safety and Health) method 5040 temperature profile (Birch and Cary, 1996;Jung et al, 2010). External calibration was performed using known amounts of sucrose.…”
Section: Organic Carbon/elemental Carbon Analysismentioning
confidence: 99%
“…The ω measured by ground-based remote sensing (0.9-0.93) is ∼ 10 % higher than values measured at the surface (0.8-0.9) (Cheng et al, 2015). From one year's worth of observations in Seoul, South Korea, a trend of increasing ω with wavelength was observed during Asian dust events, whereas little spectral dependence of ω was observed during LRT haze events (Jung et al, 2010). During the Campaign of Air Quality Research in Beijing 2006(CAREBeijing-2006, ω was found to be closely related to the inflow of air to Beijing.…”
Section: Introductionmentioning
confidence: 79%